Phylogenetic analysis of vitamin B12-related metabolism in Mycobacterium tuberculosis - Young, Douglas B.; Comas, Iñaki; de Carvalho, Luiz P. S. (Frontiers in Molecular Biosciences, 2015)
Comparison of genome sequences from clinical isolates of Mycobacterium tuberculosis with phylogenetically-related pathogens Mycobacterium marinum, Mycobacterium kansasii and Mycobacterium leprae reveals diversity amongst genes associated with vitamin B12-related metabolism. Diversity is generated by gene deletion events, differential acquisition of genes by horizontal transfer, and single nucleotide polymorphisms with predicted impact on protein function and transcriptional regulation. Differences in the B12 synthesis pathway, methionine biosynthesis, fatty acid catabolism, and DNA repair and replication are consistent with adaptations to different environmental niches and pathogenic lifestyles. While there is no evidence of further gene acquisition during expansion of the M. tuberculosis complex, the emergence of other forms of genetic diversity provides insights into continuing host-pathogen co-evolution and has the potential to identify novel targets for disease intervention.